Alabanda Payandalı Sarnıç’ta Bulunan Geç Antik Dönem Seramikleri | Late Antique Pottery from the Pillard Cistern in Alabanda - Ayşegül SOSLU (Arkhaia Anatolika, 2019)
Alabanda, which is a Carian city, is located about 7 km west of Çine District in Aydın Province and west of Marsyas (Çine) Stream. Archaeological excavations were conducted in 2012 and 2013 in the northeast of the city center and a two-roomed Pillared Cistern was discovered here. Sseven pools and terracotta pipes and “U” shaped gutter pieces for water collection and drainage systems were exposed in this building. Pottery fragments dating back from the 3rd century BC up to the 7th century AD was found in the cistern. In this study, a total of 24 artifacts, two ampullae, five pots, four oil lamps, four lekanes and nine unguentaria were evaluated. These potteries, which were studied in five groups, were dated from 6th century to 7th century AD by analogical comparison with similar samples. Potteries show that Roman dominance in Alabanda has a long history and continued until the 7th century AD. The potteries found in the cistern excavation provided important data both in the dating of the building and in the discovery of the connections of the city with the centers close to the region. In line with these findings, it was found that Alabanda continued to exist during the Roman Period and in this process, it had connections especially with its neighboring cities Nysa, Myndos, Tralleis, Stratonikeia and Caunos. In addition, Alabanda also has connections with Magnesia ad Meandrum, Laodicea, Phokaia, Demre, Kibyra, Andriake, Patara, Perge, Side and Kyzikos. Potteries classified as chronological and typological and similar examples found in other cities reveal the dimensional status of the relation of Alabanda with contemporary cities.